GROWTH AND PRODUCTION OF THREE POTATO CULTIVARS AS AFFECTED BY ORGANIC FOLIAR NUTRITION - Fadhil Hussein Al-Sahaf ,Mohammed ZedanK (Kufa Journal for Agricultural Sciences)
An  experiment was carried out in private farm in Radwaniah , 30 km westernsouth of Baghdad to test the impact of foliar spray by two organic fertilizers( Humistar and Vegeamino ) at three concentrations ( 0 , 1.0 and 1.5 ml.L-1 ) on three potato cultivars ( Ajiba , Riviera and Cardinal ) grade Elite . Plants were fertilized by using soil addition with N , P and K at rate of 120 : 60 : 200 kg.ha-1 applied to the soil.  Foliar spray was applied twice to drip point , first at 45 days and second at 65 days post planting . Split – plot experiment design experiment was implemented where 15 treatment in each replication and three replicates were used.